Burkina Faso's infrastructure : A continental perspective - Briceno-Garmendia, Cecilia; Dominguez-Torres, Carolina (2012)
Infrastructure contributed 1.3 percentage points to Burkina Faso's annual per capita gross domestic product (GDP) growth over the past decade, much of it due to improvements in information and communication technology (ICT). Raising the country's infrastructure endowment to that of the region's middle-income countries (MICs) could boost annual growth by more than 3 percentage points per capita. Burkina Faso has made significant progress developing its infrastructure in recent years, especially in the ICT sector. The country has also moved forward in the areas of road maintenance and water and sanitation, but still faces challenges in these sectors, as well as in the electricity sector. As of 2007, Burkina Faso faced an annual infrastructure funding gap of $165 million per year, or 4 percent of GDP. That gap could be cut in half by the adoption of more appropriate technologies to meet infrastructure targets in the transport and the water and sanitation sectors. Even if Burkina Faso were unable to increase infrastructure spending or otherwise close the infrastructure funding gap, simply by moving from a 10- to 18-year horizon the country could address its efficiency gap and meet the posited infrastructure targets.